Shipbuilding and Ship Repair Workers around the World (2017)
Maritime trade is the backbone of the world’s economy. Around ninety percent of all goods are transported by ship, and since World War II, shipbuilding has undergone major changes in response to new commercial pressures and opportunities. Early British dominance, for example, was later undermined in the 1950s by competition from the Japanese, who have since been overtaken by South Korea and, most recently, China. The case studies in this volume trace these and other important developments in the shipbuilding and ship repair industries, as well as workers’ responses to these historic transformations.